Room of Hazards: A Comparison of Differences in Safety Hazard Recognition Among Various Hospital-Based Healthcare Professionals and Trainees in a Simulated Patient Room. Issue 6 (17th September 2022) - Wang, Melinda; Banda, Barbara; Rodwin, Benjamin A.; Merchant, Naseema B.
Abstract : Objectives: Adverse events in hospitals are common. While studies have used simulated patient rooms to assess healthcare trainees' skills in detecting safety hazards, few have explored the characteristics of safety hazards that make them more or less identifiable to healthcare workers. We sought to determine differences in hospital-based safety hazard identification among physicians, nurses, and other staff members. Methods: Healthcare workers were invited to identify safety hazards in a simulated patient room with intentionally placed hazards. Responses were transcribed and compared between physicians (MD), nurses (RN), and other hospital-based healthcare professionals and trainees (other). Data were analyzed using nonparametric statistical analysis. Results: Twelve physicians, 29 nurses, and 26 other staff members participated in this study. Different professions identified different numbers of total hazards with nurses identifying more hazards than other professions (RN: 9.59, MD: 9.17, other: 6.35; P = 0.001). All professions had difficulty identifying hazards associated with omission (e.g., no precaution sign: MD: 8.3%, RN: 3.4%, other: 0%) or hazards requiring 2-step logical thinking (e.g., intravenous heparin for patient with head laceration: MD: 0%, RN: 6.9%, other: 0%). Conclusions: Physicians, nurses, and others identified different numbers of total hazards, and few participants identified hazards associated with omission or 2-step logical thinking. While previous studies have found differences in types of hazards identified among different healthcare members, we identified hazards that were collectively challenging for all participants to identify. Future studies should target identification of these types of hazards, using human factor engineering to decrease risk of patient harm.